African spirituality in the Johane Masowe Chishanu religious movement in Zimbabwe: A Christian church-sect dichotomy - Musoni, Phillip (HTS teologiese studies, 2021)
This study explored the impact of African indigenous spirituality on African indigenous churches (AICs), particularly in the Zimbabwean context, a special focus was on the Johane Masowe Chishanu (JMC) religious movement spirituality. The spirituality of the JMC religious movement is examined by cross-examining its denigration of the centrality of the Bible, the historical Jesus and the temple gathering as the movement appropriates and re-socialises traditional African shrines for religious gatherings. Thus, the following questions are raised in this study: is the appropriation and resocialisation of African traditional shrines, the denigration of the Bible and the disregarding of the historical Jesus for salvation by the JMC a conscious or unconscious move? If it is a conscious move, the follow-up question is: what motivates the JMC religious movement to regard such religious shrines, whilst disregarding the Bible and Jesus for its spirituality and, because of this, does the JMC religious movement retain the label ‘a Christian church’ or has become a sect?Contribution: While majority of African scholars were celebrating the proliferation of Christianity in the continent as evidenced by an unremitting mushrooming of African Indigenous Churches, some Zimbabwean scholars were categorizing Johane Masowe Chishanu church a sect. Therefore, this article examine the veracity and provenances of the Johane Masowe Chishanu church-sect dichotomy in Zimbabwe.